Examining the Determinants of Police Department Online Transparency - Chanin, Joshua M. (Criminology, criminal justice, law & society, 2017)
This study draws on the economic principle of supply and demand to examine police department online transparency. A sample of 350 department websites was evaluated using a 26-point index. To explain variation among the resultant transparency scores, several hypotheses are tested in order to identify the determinants of agency openness. Six hypotheses are driven by the notion that public demand—in the form of federally led organizational reform, legislation mandating data dissemination, and the presence of independent, civilian oversight—will correlate with increased transparency. Three others predict that ‘supply’ indicators, characteristics reflective of departmental openness, including the use of community policing strategies, the pursuit of agency accreditation, and voluntary participation in a longitudinal research study, will be positively correlated with openness. Results from several multiple regression models show support for three of nine hypotheses, with broad implications for both theory and public policy.